PROTOTYPE OF AN ARDUINO-BASED WATER QUALITY MONITORING EQUIPMENT FOR OPTIMIZATION OF BIOFLOC SYSTEMS - Jatmiko, Mukhammad Fiyan (Indonesian Applied Physics Letters, 2022)
The disadvantage of this biofloc system cultivation is that it requires intense monitoring of water quality to maintain floc stability in the cultivation media. The solution to this problem is the creation of a prototype water quality monitoring tool in a biofloc system cultivation pond that is able to measure water quality consisting of DO, temperature, pH, and ammonia and is able to display measurement data into applications and is able to provide treatment suggestions. Create prototyping with a microcontroller system as well as designing applications and carrying out testing experiments on component units. The prototype accuracy test is carried out by comparing the results of water quality measurements with conventional tools. The results of the study explained the procedure for making a prototype of a tool consisting of the design of a water quality measuring device and the design of a viewer application of water quality measurement results. The accuracy of the tool components of the DO sensor is 98.5%, the temperature sensor is 99.89%, the pH sensor is 95.1%, and the ammonia sensor is 95.4%. This tool is able to take measurements well and is useful for the breeder.